Potentiometric Titration of Lead(II) by Iodide in Acetone and Formation of Complex PbI3 – - Aziz Ramadan, Abdul; Mandil, Hasna; Maktabi, Mohammad (Asian Journal of Chemistry, 2010)
Potentiometric and differential potentiometric titrations of Pb2+ by iodide in acetone using different indicator electrodes: Pb, Cu and Pt were studied. Two end-points were observed, the first one according to the following equation: Pb2+ + 2I– → PbI2↓. While, the second end-point according to the following equation: PbI2↓ + I– → PbI3 –. The following complex PbI3 – is formed in acetone solution, for the first time, a clearly and consistently log K = -21.92 (dissociation constant) is obtained. Solubility product (SP) of the deposit (PbI2↓) is calculated, the values of log SPPbI2↓ were between -18.30 to -18.80. A 103.5 μg of Pb2+ was determined with relative standard deviation not to exceed ± 3.1 %.